(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Pottery played a significant role not only in our day-to-day life but also in religious practices and trade in Indian society. Pottery made by potters is eco-friendly. It is important for both economic and cultural aspects. So, in this regard, this study is an attempt to know the characteristic features of the potter community of the Chenga development block and their problem and prospects. The study is descriptive in nature. The study reveals that though the things made by potters have importance in our daily life, due to modernization and changing consumer preferences, nowadays they have faced various challenges in their occupations. And the potters of this region, they belong to scheduled castes communities.